SYNTACTIC AND PRAGMA-SEMANTIC NATURE OF EXCITATIONS - Mardiyeva Khurshida Tolibjon qizi (International Journal of Literature and Language Studies, 2026)
This article examines the interpretation of encouragement in contemporary Uzbek linguistics from a communicative-pragmatic perspective. It analyzes their syntactic independence, positional features within sentences, intonational characteristics, and pragmatic functions in speech.